2023
DOI: 10.1590/1413-7054202347007522
|View full text |Cite
|
Sign up to set email alerts
|

Cachaça sold in polyethylene terephthalate packaging: Determination of the physical-chemical profile, polycyclic aromatic hydrocarbons and ethyl carbamate

Abstract: The production of cachaça in Brazil is a historical and cultural practice that has been gaining ground in the commercial sector with the marketing of its product with new labels, derivatives and different types of packaging for the beverage. Polyethylene Terephthalate (PET) packaging has been used by some producers because of its lower cost and greater durability for transport. The influence of storage on 15 samples of commercial cachaça packed in polymeric packaging was investigated. The physical-chemical qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Barbosa et al [173] examined cachaça stored in PET packaging and revealed that the beverages contained high concentrations of chemicals outside the limits of Brazilian Quality Standards. They analysed 15 commercial cachaça samples stored in polymeric packaging to investigate the influence of storage on their physical-chemical quality and the presence of PAHs.…”
Section: Pah In Cachaça Productionmentioning
confidence: 99%
“…Barbosa et al [173] examined cachaça stored in PET packaging and revealed that the beverages contained high concentrations of chemicals outside the limits of Brazilian Quality Standards. They analysed 15 commercial cachaça samples stored in polymeric packaging to investigate the influence of storage on their physical-chemical quality and the presence of PAHs.…”
Section: Pah In Cachaça Productionmentioning
confidence: 99%